2017
DOI: 10.21273/horttech03559-16
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry Cultivar Evaluation under High-tunnel and Organic Management in North Carolina

Abstract: High-tunnel strawberry (Fragaria ×ananassa) production for extended seasons has a great economic potential for small farmers. However, information on cultivars that are suitable for high tunnels is rather limited. In this study conducted in the 2014–15 season, strawberry plugs of eight June-bearing cultivars (Florida Radiance, Benicia, Camarosa, Camino Real, Chandler, Strawberry Festival, Sweet Charlie, and Winterstar) and two day-neutral cultivars (San Andreas and Albion) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 18 publications
6
22
1
Order By: Relevance
“…Both cultivars have better fruit quality compared with other day-neutral cultivars and June-bearers (Ballington et al, 2008;Ruan et al, 2013;Tudor et al, 2014). In our pervious cultivar evaluations, 'Albion' and 'San Andreas' had earlier fruit harvest than June-bearers (Gu et al, 2017b).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Both cultivars have better fruit quality compared with other day-neutral cultivars and June-bearers (Ballington et al, 2008;Ruan et al, 2013;Tudor et al, 2014). In our pervious cultivar evaluations, 'Albion' and 'San Andreas' had earlier fruit harvest than June-bearers (Gu et al, 2017b).…”
mentioning
confidence: 68%
“…Most of these studies used June-bearing cultivars. Our previous varietal trials also proved that, with the help of rowcovers, strawberry could be successfully produced through winter, although unpredictable low temperatures in winter could cause chilling damage to fruit (Gu et al, 2017b). Additional winter protections such as adding low tunnels (LT) inside HT, may lead to reliable winter harvests.…”
mentioning
confidence: 92%
“…A strawberry study conducted in FL found 54% greater yields and marketable fruit weight 69% greater under high tunnels compared with open field production (Salame-Donoso et al, 2010). In NC, differences among strawberry cultivars correlated with greater yields under high tunnels indicating the importance of crop and cultivar selection (Gu et al, 2017). An organic tomato study in NC found that heirlooms grown under high tunnels in the spring and summer had equal or greater yields depending on the year, and they were consistently harvested three weeks earlier than the field (O'Connell et al, 2012).…”
mentioning
confidence: 99%
“…An early spring lettuce crop in TN achieved not only greater total yields under high tunnels compared with the field but the crop was also subject to more pest, disease, and physiological damage, reducing marketability of the crop (Wallace et al, 2012). Two studies (GA and NC) found that early blooming of small fruits (i.e., strawberry and Southern highbush blueberry) under high tunnels may increase frost damage and fruit abortion because of early bloom times (Gu et al, 2017;Ogden and van Iersel, 2009). Overall, high tunnels appear to offer a benefit in the region but yearly weather conditions, structure/system characteristics, cultivar selection, and crop sensitivity to fluctuating temperatures may affect potential yield gains.…”
mentioning
confidence: 99%
“…Area ( trialing new cultivars from a number of breeding programs; this may lead to a wider selection of cultivars that are planted in the future. There is continued interest in season extension through the use of low and high tunnels and row covers, especially where produce can be sold at local markets (Gu et al, 2017). The early success of the industry in this region is due, in part, to the use of MB as a soil fumigant to control soil-borne pests.…”
Section: Statementioning
confidence: 99%